Performance-Sensitive Debt - Manso, Gustavo; Strulovici, Bruno; Tchistyi, Alexei (Review of Financial Studies, 2010)
[This article studies performance-sensitive debt (PSD), the class of debt obligations whose interest payments depend on some measure of the borrower's performance. We demonstrate that the existence of PSD obligations cannot be explained by the trade-off theory of capital structure, as PSD leads to earlier default and lower equity value compared to fixed-rate debt of the same market value. We show that, consistent with the pecking-order theory, PSD can be used as an inexpensive screening device, and we find empirically that firms choosing PSD loans are more likely to improve their credit ratings than firms choosing fixed-interest loans. We also develop a method to value PSD obligations allowing for general payment profiles and obtain closed-form pricing formulas for step-up bonds and linear PSD.]